STUDI PERBANDINGAN DUA KELOMPOK UMUR TERHADAP MULA KERJA DAN MASA KERJA ANESTETIKA LOKALPADA KASUS PENCABUTAN GIGI MOLAR I ATAU MOLAR II ATAS - Kholifa, Mahmud (Universitas Muhamadiyah Surakarta, 2011)
Effect of inï ltration due to the action of anesthesiasubstance on terminal nerve ï bers maxillary molars the anesthesiaï uid ï ow through the bone viahavers channels.This study is a quasi-experimental studies (clinical trials), which aims to determine the difference of onset and durationLidocaine between age groups 15-24 years age group 25-34 years in the case of extraction a molar tooth I or II maxilla conducted on patients who came to the Polyclinic FKG UGM, Yogyakarta. The number of samples obtained was 34 samples divided into two groups, Group I were patients with 15-24 years of age or younger, group II is patients aged 25-34 years or older. The data obtained areonset and duration of the age group 15-24 years compared with onset and duration of Lidocaine in the age group 25-34 years. The data obtained were analyzed by t-test with signiïcance level (p <0.05). The results of this study indicate that there are no signiï cant differences between the onsetLidocaine in the age group 15-24 years with onset on the Lidocaine group 25-34 years. There is also a non-signiï cant difference between Lidocaineduration in the group aged 15 - 24 years with a duration of Lidocaine on the group 25-34 years at p <0.05. The mean - median onsetLidocaine in the age group 15-24 years was 60.3 seconds with a range between 22-95 seconds while the onset on the Lidocaine group 25-34 years was 55.5 seconds with a range between 14-111 seconds. The mean - average durationLidocaine in the age group 15-24 years was 162.59 minutes with a range between 120-195 minutes while the duration of Lidocaine on the group 25-34 years was 184.41 with a range between 120-330 minutes.